Roles of values in the risk factors of passive suicide ideation among young adults in the US and Japan - Taku, Kanako; Arai, Hirokazu (Frontiers in Psychology, 2023)
The present study examined how the importance of values and perceived value congruence with families, friends, and country would be associated with the risk factors of passive suicide ideation. Specifically, the study investigated the associations that the values and perceived congruence had with thwarted belongingness and perceived burdensomeness during the COVID-19 pandemic after controlling for the impact of depression levels. The data from the US and Japan demonstrated that the values such as cherishing family and friends and value congruence played a protective factor for Japanese participants; however, the associations differed among those in the US. Values such as enduring challenges played a protective factor for perceived burdensomeness in Japan whereas values such as cherishing family and friends played a protective factor and improving society was a risk factor for thwarted belongingness for those in the US. These results can be used to further understand the roles of values in mental health.